2008
DOI: 10.1007/s00404-008-0844-8
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine and immune cell levels in peritoneal fluid and peripheral blood of women with early- and late-staged endometriosis

Abstract: The result of this study did not show any significant difference in PB and PF cytokine and lymphocyte subgroups between normal and early- and late-staged endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 22 publications
3
23
1
3
Order By: Relevance
“…Markers of inflammation appear to be useful as diagnostic markers for endometriosis. Serum IL levels, urocortin, or vitamin D binding globulin would bring high costs and have no chance for use in the hospital setting (1,8,9). Cho et al (22) showed that NLR alone or in combination with Ca-125 would offer an inexpensive and practical method for the diagnosis of endometriosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Markers of inflammation appear to be useful as diagnostic markers for endometriosis. Serum IL levels, urocortin, or vitamin D binding globulin would bring high costs and have no chance for use in the hospital setting (1,8,9). Cho et al (22) showed that NLR alone or in combination with Ca-125 would offer an inexpensive and practical method for the diagnosis of endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…Barrier et al (7) reported functionally altered immune cells in peritoneal circulation of patients with endometriosis and suggested sterile inflammation occurring in the peritoneal cavity. Based on this inflammatory response in endometriosis, urocortin 2, urocortin 3, high sensitivity c reactive protein (CRP), interleukin 2 (IL-2), interleukin 4 (IL-4), interleukin 10 (IL-10), interferon γ (IFN-γ) and lymphocyte count have been examined alone and in combination with Ca-125 for detecting endometriosis (8,9). Neutrophil/lymphocyte ratio (NLR) and platelet/lymphocyte ratio (PLR) in peripheral blood are simple systemic inflammatory response (SIR) markers which are evaluated by blood parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, matrix metalloproteases favor angiogenic sprouting by cleaving the extra-cellular matrix, particularly MMP2, which production is stimulated by the activity of endometriotic cells in the peritoneal fluid. 35 Platelet-derived growth factor B (PDGF-B) is regarded as the main promoter of the pericyte investment in neovessels, being significantly over-expressed by eutopic endometrium of endometriosis patients. 4 Many other ubiquitously expressed molecules have been found to enhance angiogenesis in vitro, in animal models of endometriosis and/ or in human samples.…”
mentioning
confidence: 99%
“…Outro biomarcador de interesse do presente estudo é o CD-23 solúvel, uma proteína que se expressa na superfície da membrana celular (Kijimoto-Ochiai, 2002;Getahun et al, 2005), comumente identificada como receptor de baixa afinidade para IgE em células B, eosinófilos, monócitos, células dendríticas, epiteliais, células de Langerhans e plaquetas (Hassa et al, 2009;Rambert et al, 2009 …”
Section: Cd-23 Solúvelunclassified
“…Avaliação do CA-125 e do CD-23 solúvel em pacientes com endometriose pélvica Discussão O CA-125 tem sido bastante estudado na literatura e é considerado um exame útil para o diagnóstico clínico da endometriose (Abrão et al, 1997;Kafali et al, 2004;Ghaemmaghami et al, 2007;Hassa et al, 2009). O CD-23, menos avaliado, mostrou ter concentrações elevadas em fluído peritoneal de mulheres com endometriose, fato sugestivo da ativação de células B e indicativo de possível desbalanço do sistema imune humoral, como ocorre nessa doença (Odukoya et al, 1996a;Matalliotakis et al, 2000;Matalliotakis et al, 2001).…”
Section: Cd-23 Solúvelunclassified